Study on game-based incentive mechanism of mobile ad hoc network - Ying-you WEN; Bo ZHAO; Hong ZHAO (Tongxin xuebao)
According to the selfishness of rational mobile ad hoc network nodes showed during the packet forwarding, the selfish behavior statically and dynamically based on game theory were analyzed and modeled. A stern tit for tat strat-egy(STFT) was proposed to motivate node cooperation, and an infinite repeated game model was established to analyze the node behavior. Then, an incentive-compatible condition was obtained analytically. The dynamic process of selfish node turning to cooperate using the evolutionary game theory was studied, and the evolutionary stability of STFT was proved. Simulation results show that, even if the ratio of selfish nodes is one, by setting punishment parameters reasona-bly, the overall network performance can be improved 80% at most.